Scholarship in Emergency Medicine: A Primer for Junior Academics: Part II: Promoting Your Career and Achieving Your Goals - Langabeer, James (West J Emerg Med, 2018)
Scholarship is an important component of success for academic emergency physicians. Scholarship can take many forms, but all require careful planning. In this article, we provide expert consensus recommendations for improving junior faculty’s scholarship in emergency medicine (EM). Specific focus is given to promoting your research career, obtaining additional training opportunities, networking in EM, and other strategies for strategically directing a long-term career in academic medicine.